Effects of Pinus massoniana bark extract on the invasion capability of HeLa cells. (June 2016) - Li, Ying-Ya; Feng, Jiao; Zhang, Xiao-Lu; Li, Meng-Qi; Cui, Ying-Yu
Highlights: Pinus massoniana bark extract (PMBE) is rich in proanthocyanidins. HeLa cells can metastasise across Matrigel ® . PMBE inhibits invasion of HeLa cells by down-regulation of cathepsin B expression. Proanthocyanidins, an ingredient of functional foods, may be used as a part of a future anti-tumour metastasis agent. Abstract: Pinus massoniana bark extract (PMBE) is a natural product developed in China, with flavonoids, especially proanthocyanidins, as its main components. Flavonoids are shown to inhibit the abnormally high expression of cathepsin B (CatB) in some tumour cells. CatB is normally located in lysosomes and plays a role in the autophagy process. However, if the cells turn malignant, CatB may secrete and take part in the metastasis of cancer cells. Some researchers have reported that PMBE can inhibit the migration of HeLa cells. Thus, this research aimed to examine whether PMBE inhibits the invasion of HeLa cells. We first confirmed the metastasis capability of HeLa cells and then explored the effects of PMBE on the expression of CatB. Our results proved that HeLa cells can metastasise across a Matrigel ® matrix and this invasion capability can be significantly inhibited by PMBE, possibly by down-regulating the expression of CatB, mainly at the transcriptional level.